Pengaruh Pertumbuhan Industri Terhadap Kualitas Air Bersih di Daerah Perkotaan - Susatyo Adhi Pramono; Chrisna Pudyawardhana (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2018)
The increase in industrial growth will be followed by the emergence of side effects, namely the emergence of industrial waste. The waste can be solid wastes, liquid wastes or gaseous wastes. With the increasing number of population, the more waste will be produced in the form of domestic waste, industrial waste and other wastes. In addition to producing products that are beneficial to society, industrialization also has an impact, among others, the production of hazardous and toxic waste materials, which, if discharged into environmental media, can threaten the environment, health and survival of humans and other living things. Industrial growth will have an impact on the increase in industrial waste that will be produced. Therefore, it is also necessary to think about whether the industry produces hazardous waste or not, so it is necessary to determine whether or not to provide waste treatment and how to handle the waste. New industrial wastewater may be discharged into water bodies if it meets the requirements set by the Government. A wastewater treatment plant, is a structure designed to remove biological and chemical waste from water so as to allow the water to be used in other activities. The goal of WWTP is to filter and clean water that has been contaminated by both domestic and industrial chemicals.